Solution Concentration Influence on the Performance of a Diffusion Absorption Refrigeration System Using Different Refrigerant Blend - Valiyandi, S.; Thampy, G. (Journal of Scientific Research, 2025)
Diffusion absorption refrigeration technology is highly intriguing field of research in current times owing to its low or no power requirement. The diffusion absorption refrigeration system is operated by waste heat or renewable energy sources. Numerous studies worldwide have investigated various refrigerant blends to identify the best performing option, which exhibits the lower global warming potential and emits the fewest greenhouse gases. Generally, a diffusion absorption refrigeration (DAR) system operates with three fluids, namely water, helium and ammonia. The objective of this study is to investigate the performance of DAR systems using five alternative refrigerant combinations, aiming to replace conventional refrigerant blend, and to examine the influence of rich solution concentration. The refrigeration performance metrices, including cooling capacity, performance coefficient, heat supplied to the generator and exergy are estimated for various refrigerant blends. The results of this study reveals that the diffusion absorption refrigeration systems utilizing isobutane, dimethyl formamide, and helium mixtures achieve optimal performance at lower rich solution concentration compared to other refrigerant combinations.